Beyond boundaries: Neuroprotective effects of steroids and ecdysteroids in SH‐SY5Y cells ‐ A systematic review - Bizhar Ahmed Tayeb; Isaac Kinyua Njangiru; Renáta Minorics (Neuroprotection, 2024)
Abstract Steroids and ecdysteroids have been shown to exhibit a range of biological effects, including anti‐inflammatory, anticancer, and neuroprotective. This systematic review aims to highlight the evidence‐based neuroprotective and antioxidant effects of steroids and ecdysteroids in SH‐SY5Y neuroblastoma cells. A comprehensive literature search was conducted on May 11, 2023, without publication source restrictions, using various electronic databases, including PubMed, Web of Science (WoS), Scopus, and Cumulative Index to Nursing and Allied Health Literature. Of 103 articles, only 20 studies were included for investigating the neuroprotective effects of steroids and ecdysteroids in SH‐SY5Y cells exposed to oxidative stress or neurotoxic agents. The risk of bias and quality assessment of the included studies were evaluated in accordance with the Nature Publication Quality Improvement Project specific criteria. The selected studies reported the antioxidant effects of the tested compounds on SH‐SY5Y cells and demonstrated their ability to scavenge free radicals and prevent lipid peroxidation. These findings suggest that neurosteroids have potential therapeutic applications for the prevention and treatment of neurodegenerative diseases characterized by oxidative stress and neuronal damage. Some studies have investigated the molecular mechanisms underlying the neuroprotective and antioxidant effects of steroids and ecdysteroids in SH‐SY5Y cells. These mechanisms include the activation of antioxidant enzymes, such as superoxide dismutase and glutathione peroxidase, and the modulation of various signaling pathways, including the phosphoinositide 3‐kinase/protein kinase B and mitogen‐activated protein kinase/extracellular signal‐regulated kinase pathways. This review provides evidence that the tested compounds have remarkable neuroprotective and antioxidant effects in human neuroblastoma SH‐SY5Y cells.